A novel Staphylococcus aureus biofilm phenotype mediated by the fibronectin-binding proteins, FnBPA and FnBPB. - FOSTER, TIMOTHY JAMES (My University, 2008)
Device-associated infections involving biofilm remain a persistent clinical problem. We recently reported that four methicillin-resistant Staphylococcus aureus (MRSA)strains formed biofilm independently of the icaADBC-encoded exopolysaccharide. Here, we report that MRSA biofilm development was promoted under mildly acidic growth conditions triggered by the addition of glucose to the growth medium. Loss of sortase, which anchors LPXTG-containing proteins to peptidoglycan, reduced the MRSA biofilm phenotype. Furthermore introduction of mutations in fnbA and fnbB, which encode the LPXTG-anchored multifunctional fibrinogen and fibronectin-binding proteins, FnBPA and FnBPB, reduced biofilm formation by several MRSA strains. However, these mutations had no effect on biofilm formation by methicillin-sensitive S. aureus strains. FnBP-promoted biofilm occurred at the level of intercellular accumulation and not primary attachment. Mutation of fnbA or fnbB alone did not substantially affect biofilm, and expression of either gene alone from a complementing plasmid in fnbA fnbB mutants restored biofilm formation. FnBP-promoted biofilm was dependent on the integrity of SarA but not through effects on fnbA or fnbB transcription. Using plasmid constructs lacking regions of FnBPA to complement an fnbAB mutant revealed that the A domain alone and not the domain required for fibronectin binding could promote biofilm. Additionally, an A-domain N304A substitution that abolished fibrinogen binding did not affect biofilm. These data identify a novel S. aureus biofilm phenotype promoted by FnBPA and FnBPB which is apparently independent of the known ligand-binding activities of these multifunctional surface proteins.
PUBLISHED
Keywords: WALL-ASSOCIATED PROTEIN;; SURFACE PROTEIN;